Common and biased signaling pathways of the chemokine receptor CCR7 elicited by its ligands CCL19 and CCL21 in leukocytes. Issue 6 (4th January 2016) - Hauser, Mark A.; Legler, Daniel F.
Abstract : Review on how distinct signal transduction events control CCR7‐driven lymphocyte and DC activation and migration. Abstract : Chemokines are pivotal regulators of cell migration during continuous immune surveillance, inflammation, homeostasis, and development. Chemokine binding to their 7‐transmembrane domain, G‐protein‐coupled receptors causes conformational changes that elicit intracellular signaling pathways to acquire and maintain an asymmetric architectural organization and a polarized distribution of signaling molecules necessary for directional cell migration. Leukocytes rely on the interplay of chemokine‐triggered migration modules to promote amoeboid‐like locomotion. One of the most important chemokine receptors for adaptive immune cell migration is the CC‐chemokine receptor CCR7. CCR7 and its ligands CCL19 and CCL21 control homing of T cells and dendritic cells to areas of the lymph nodes where T cell priming and the initiation of the adaptive immune response occur. Moreover, CCR7 signaling also contributes to T cell development in the thymus and to lymphorganogenesis. Although the CCR7–CCL19/CCL21 axis evolved to benefit the host, inappropriate regulation or use of these proteins can contribute or cause pathobiology of chronic inflammation, tumorigenesis, and metastasis, as well as autoimmune diseases. Therefore, it appears as the CCR7–CCL19/CCL21 axis is tightly regulated at numerous intersections. Here, we discuss the multiple regulatory mechanism of CCR7 signaling and its influence on CCR7 function. In particular, we focus on the functional diversity of the 2 CCR7 ligands, CCL19 and CCL21, as well as on their impact on biased signaling. The understanding of the molecular determinants of biased signaling and the multiple layers of CCR7 regulation holds the promise for potential future therapeutic intervention.